The auditor and the law / Rohani Mohd. Shah (Universiti Teknologi MARA, Terengganu, 1992)
Auditors, in any company stands in a unique and special postition. He is the one who prepares a 'true and fair view" of the company's Profit and Loss Account, an accounting document which is open for public inspection at anytime. Thus, in order to perform his duty, he has to be the" watchdog" of the company. However, this obligation is regulated by the Companies Act 1965. This Article deals with the laws governing the performance of his special position.